The Post-2018 Ethiopian Foreign Policy towards the Horn and Ethio-Sudan Relationships Dynamics - Abebe Tigire Jalu; Asnake Kefale Adgeh (PanAfrican Journal of Governance and Development)
Foreign policy is dynamic and constantly changes in response to major domestic, regional, or global developments. The political reform that brought Ethiopian Prime Minister Abiy Ahmed to office in 2018 exhibited an ‘inside out foreign policy approach.' Domestic issues and Ethiopian citizens were prioritized under the policy, followed by neighboring states, the continent, and the world. This article analyzes Ethiopian foreign policy towards the region and the factors shaping the post-2018 Ethio-Sudan relations. The study utilized a qualitative approach involving key informant interviews, archival materials, and an in-depth investigation of published documents and sources. Even though Ethiopia pursued an appealing foreign policy towards Sudan under the 'Horn First' ethos, factors such as border issues, domestic instabilities, the reinstatement of the mutual destabilization policy, Egypt's interest, and mutual misunderstandings concerning UAE- made their relationships dynamic, alternating between mutual suspicion and peaceful cooperation. Resolving domestic security and political crises while exploiting natural and organic bridges such as borders, shared peoples, and transboundary resources as opportunities for their integration and mutual development rather than security threats can cure the diplomatic ailment.